Potencialidades e desafios do monitoramento dos objetivos de desenvolvimento sustentável no município de Curitiba/PR - Azevedo, Marcela Evelyn Paiva de (2024)
The UN Agenda 2030, adopted in September 2015, is a global framework that establishes an ambitious vision for sustainable development. Its main pillars are the 17 Sustainable Development Goals (SDGs), which include interconnected and integrated goals, designed to guide national and international actions until the year 2030. The municipality of Curitiba, the object of this study, seeks to align complies with the SDGs, coordinates efforts between government entities, the private sector, civil society and its citizens, aiming to create integrated policies, allocate efficient resources and stimulate technological innovation to achieve these global goals in a locally relevant way and impactful. The main objective of this research was to analyze the potential and challenges of monitoring the SDGs in the city of Curitiba. The theoretical foundation covers indicators of sustainability, sustainable development and the 2030 Agenda. Considering the data released by the city hall and other secondary sources, the methodology used was qualitative, applied to the reality of the municipality. For this, the method adopted was bibliographic and documentary review and bibliometric analysis of relevant sources of scientific production. For data collection, bibliographic and documentary survey of secondary sources was used. In the analysis and discussion of the results, the main indicators of each goal were selected, adapted to the reality of Curitiba. In this way, based on the analysis of the data collected, it was possible to identify how Curitiba has positioned itself in terms of achieving the SDGs. The actions implemented by the municipality related to each SDG, their strengths and weaknesses, were evaluated. Finally, the results show that there is still a lot to be done at the local level, the data that is released by the municipality still needs refinement and better dissemination of the information collected. It was concluded that despite the advances, Curitiba still faces challenges in meeting the 17 Sustainable Development Goals (SDGs) regarding the organization of local indicators, their compliance, as the main platform lacks information, brings incomplete information or interpreted differently than expected by national and global goals.